Women in business: The impact of digital and financial literacy on female-owned small and medium-sized enterprises - Nadia Asandimitra; Achmad Kautsar; Dewie Tri Wijayati; Nunik Dwi Kusumawati; Ina Uswatun Nihaya (Investment Management & Financial Innovations)
The growth of small and medium enterprises (SMEs) shows a positive trend and has even become a major highlight in the national economic landscape. Moreover, most of these businesses are owned by women. Examining how digital capability and financial literacy and a dynamic environment affect the success of female-owned small and medium-sized enterprises in Indonesia is the main goal of this study. Financial and digital capability are examined as mediators between performance and these factors. The study used a causal explanatory research approach. The data in this study were collected through questionnaires. This research surveyed 100 female-owned small and medium-sized enterprises in Indonesia’s food and beverage, herbal and pharmaceutical, fashion, and craft industries. Partial Least Square (PLS) analysis was utilized in this work as an analytical tool. The study reveals that financial literacy significantly enhances SMEs` performance by improving resource management. However, a dynamic environment alone does not impact performance unless supported by other competencies. Financial competence does not strengthen the effect of financial literacy, indicating it may not be sufficient for success. Conversely, digital competence is crucial, mediating the relationship between a dynamic environment and SMEs` performance. Therefore, SMEs with strong digital skills are better positioned to adapt and thrive, making digital competence key to sustained business success.